Draught performance of Indian camels of Bikaneri breed - RAI, A K; KHANNA, N D (The Indian Journal of Animal Sciences, 2013)
The Bikaneri camels (8-12 years) weighing 646.4±25.5 kg were subjected to payload of 2.8 kg/kg body weight on a 4-wheel cart. The camels covered 25.5 km distance in 4.9±0.08 hr at an average speed of 1.53±0.04 m/sec in a continuous work spell during summer season. The respiratory frequency, pulse rate, skin and rectal temperature increased by 314,84. 14.8 and 6.8%. respectively, over the initial values. Loss in the body weight due to work stress was 3.6%. With the increase in work stress from initial 5.1 km span to the concluding distance of 25.5 km,the speed.tractive force. work output and power output were reduced by 21.6.8.8 and 33.8% respectively. The power and work output per kg body weight decreased with the increase in live weight. Associations of draught force with some body measurements were estimated.